Isyarah ‘Ilmiyyah (Sains) dalam Al-Qur’an Surah Al-Syams Ayat 1-5 Perspektif Zaghloul Raghib Muhammad An-Najjar - Ilham Habibullah; Mahmud Rifaannudin; Ahmad Suharto; Maudi Nurhidayah (Studia Quranika, 2024)
Research on scientific signs can provide a deeper understanding of the scientific content of the Quran, but the lack of integration between Quranic scholarly studies and modern scientific studies has led to a gap in the understanding of Muslims regarding the Quran. Based on this issue, the researcher aims to uncover the scientific signs behind Surah Ash-Shams verses 1-5, such as the sun, moon, day, night, and the sky. This research refers to the commentary of Zaghloul An-Najjar due to his expertise in the field of earth sciences, making the study more effective in revealing the truth of the Quran. The research method used is qualitative with a scientific-themed maudhui commentary approach. This study is a literature review using descriptive analysis methods. The results obtained from this research are: Firstly, the immense benefits and materials of sunlight cannot be replaced by human-made alternatives. Secondly, the natural phenomena called solar and lunar eclipses. Thirdly, sunlight influences the production of serotonin hormone during the day, while the increasing darkness of the night helps the production of melatonin hormone. Fourthly, behind the visible sunlight, there is a daytime layer surrounding the earth above the Earth's atmospheric layer, allowing solar energy to reach the Earth. Finally, the vastness of the sky in outer space is discussed, leading to various galaxies and clusters of galaxies.